Cyber Troop (Pasukan Dunia Maya) Sebagai Upaya Penanggulangan Pencemaran Nama Baik di Dunia Cyber (Studi Kasus di Polda Bali) - Muhammad Alfian Dwi Saputra; I Nyoman Gede Sugiartha; Ketut Adi Wirawan (Fakultas Hukum Universitas Warmadewa, 2022)
According to technological developments, there are as many facilities available specifically in cyberspace. This technology development also tends to provide the chance of criminals, specifically crimes in cyberspace. The focus of this thesis research is to examine the definition and elements of a criminal act, the role of cyber troop in criminal acts, inhibiting factors and efforts to resolve the defamation of cyber troop carried out by the Bali Police. The method applied for the research is kind of the type of empirical juridical legal research or kind of research which tends to help examining the applicable legal provisions and also thing occurs in real way of society or kind of research that was done in actual situations of the society, the purpose is to find kind of facts which are used to be the evidence. Research data is getting analyzed in order to help identify the problems that led to problem solving. Empirical juridical research here applies a kind of statutory approach. The object is a case of defamation. The research data were collected using observation, interviews, and documentation methods and summarized using sentences that are easy to understand.